Developmental and validation of an adapted volleyball program for students with mental retardation and autism - Gozo, Marie Jane G. (2009)
The study analyzed the effects of Adapted Volleyball Program (AVP) in order to determine the sport enjoyment levels and sport participation levels of students with MR and autism. Furthermore, it sought to find the significant difference with respect to students' increase in sport enjoyment level in terms of gender and disability or condition. An 18-item modified Physical Activity Enjoyment Scale and a Systematic Observation of Students Opportunities to Respond were utilized as the main instruments of the study. Findings showed that in general, the effects of the AVP in terms of sport enjoyment level was high or positive. Moreover, the sport participation level of students with MR and autism in the adapted volleyball games was also high or positive.